Inhibition of the BMP pathway prevents development of Barrett's-associated adenocarcinoma in a surgical rat model. Issue 5 (28th October 2021) - Westra, Wytske M; Straub, Danielle; Milano, Francesca; Buttar, Navtej S; Wang, Kenneth K; Krishnadath, Kausilia K
Summary: Introduction: Esophageal adenocarcinoma (EAC) is an aggressive cancer, associated with reflux esophagitis and intestinal metaplasia (IM). One underlying biological mechanism, which possibly drives the development of EAC, is the dysregulated expression of Bone Morphogenetic Proteins (BMPs). Aim: To investigate if local delivery of Noggin, a BMP antagonist, reduced EAC. Methods: After obtaining proof of principal on local delivery of a Noggin/Sucralfate substance, a randomized controlled trial to test the effects of Noggin on EAC development was performed in a surgical rat model. In the model, an esophago-jejunostomy leads to development of reflux-esophagitis, IM and eventually EAC. Rats were treated by Noggin/Sucralfate or Sucralfate alone. Treatment was administered from 26 to 29 weeks after the operation. Results: Of the 112 operated rats, 52 survived beyond 26 weeks. Finally, 25 rats treated with Noggin/Sucralfate and 21 with Sucralfate, were evaluated. At the end, 39 (85%) of the animals had IM while 28 (61%) developed cancer. There were significantly more cancers in the Noggin/Sucralfate arm (50%) versus the Sucralfate group (73%) (Chi square, P < 0.05). Most cancers were mucous producing T3 adenocarcinomas. There were no significant differences in the amount of IM, size or grade of the cancers, or expression of columnar and squamous markers between the two groups. Conclusion: In this study, we demonstrated that inhibition of BMPs by Noggin reduced development of EAC in a surgical esophagitis-IM-EAC rat model. In future, effective targeting of the BMP pathway with selective BMP-inhibitors could become an important asset to improve EAC patient outcome.